Fatigue Life Prediction of Welded Box Structures - Zedira, H.; Gilgert, J.; Boumaza, A.; Jodin, P.; Azari, Z.; Pluvinage, G. (Проблемы прочности, 2004)
The objective of this study is to predict fatigue life of metal welded boxes. Experimental results of fatigue life are satisfactory predicted using an analytical scheme based on the volumetric approach.